Gaining Greater Access to Western European Decision‐Makers: a Motive for Australian Membership of the OECD. (June 2014) - Carroll, Peter
<x xml:space="preserve">Abstract</x> In weighing Britain's decision to seek membership of the European Economic Community Australian scholars have focussed attention on its adverse impact on Anglo‐Australian and EU‐Australian relations, and the emphasis that Australia thereafter placed upon economic relations with Asia. This article identifies a consequence of Britain's decision which has largely escaped attention: the part it played in stimulating Australia's successful 1969 application for membership of the Organisation for Economic Cooperation and Development. Although Australia's interest in the increased access to West European decision‐makers that the OECD would provide dates to the latter 1940s and 1950s, the British application for membership of the EEC added particular weight to those arguing that Australia should seek OECD membership. It led to an extension of Australian activities in Western Europe which was not extinguished by the growing emphasis on relations with the Asian region.